Health Equity and Financial Protection Datasheets : East Asia and Pacific - Bredenkamp, Caryn; Wagstaff, Adam; Buisman, Leander; Prencipe, Leah; Rohr, Devon (World Bank, Washington, DC, 2017)
The health equity and financial protection datasheets provide a picture of equity and financial protection in the health sectors of low- and middle-income countries. Topics covered include: inequalities in health outcomes, health behavior and health care utilization; benefit incidence analysis; financial protection; and the progressivity of health care financing. This report show how health outcomes, risky behaviors and health care utilization vary across asset (wealth) quintiles and periods. Benefit-incidence analysis (BIA) shows whether, and by how much, government health expenditure disproportionately benefits the poor the distribution of subsidies depends on the assumptions made to allocate subsidies to households. This reports whether overall health financing, as well as the individual sources of finance, is regressive (i.e. a poor household contributes a larger share of its resources than a rich one), progressive (i.e. a poor household contributes a smaller share of its resources than a rich one) or proportional.